Management and communication practices in Singapore: lessons from a model economy - Rehman, Sharaf (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
With its 5.8 million inhabitants, retaining its unique version of democracy, and remaining a traditional yet progressive city, Singapore stands as a model economy for other Asian and middle eastern economies. From 1819 to 1963, Malaysia and Singapore – as one country – were a British colony. In 1963, when British rule ended and Malaysia gained her independence, Singapore remained a part of Malaysia. However, the racial tension between Malay, the ethnic Chinese, and other non-Malay groups escalated and turned violent. In 1965, Singapore cut her ties with Malaysia and became a sovereign, independent state. While retaining its collectivistic culture, Singapore has gained a competitive edge as a high-end shopping centre in the region. During the past 60 years, the Singaporean economy and businesses have shifted their focus from the manufacturing of electronic components, computer hard drives, small appliances, and garments to financial services, banking, insurance services, and asset management. Relying on data collected through interviews, observations, and a brief questionnaire, this case study of Singaporean businesses presents a description of the management styles and communication strategies of 78 business managers in Singapore, representing the service, retail, and manufacturing sectors. The data reveal that Human Resources Approach to management is the most common style of management. Analysis of communication content, style, and flow demonstrates that cultural customs such as respect for the elderly, caring for and mentoring the younger generation, loyalty to one’s family, and conformity to family traditions are the driving forces of the businesses in Singapore. The analysis suggests that it is the dominant culture of a society that shapes the business practices and business values in any given society.

W roku 2020 Singapur z 5,8 mln mieszkańców, szczególną wersją jednopartyjnej demokracji i hołdującym tradycji, choć jednocześnie postępowym społeczeństwem stał się modelową gospodarką dla innych krajów azjatyckich. Od 1819 do 1963 r. obszar Malezji i Singapuru stanowił kolonię brytyjską. W roku 1963, gdy panowanie Brytyjczyków dobiegło końca, Malezja odzyskała niepodległość, a Singapur stał się jej częścią. Taki stan nie trwał jednak długo – w efekcie narastających napięć rasowych pomiędzy Malajami, etnicznymi Chińczykami i innymi grupami w 1965 r. Singapur odciął się od Malezji i utworzył niezależne państwo. Pozostawiając swą kolektywistyczną kulturę, Singapur zyskał przewagę konkurencyjną jako ekskluzywne centrum handlowe w regionie. Przez ostatnie 60 lat singapurscy przedsiębiorcy przesunęli swoje zainteresowanie z wytwarzania komponentów sprzętu elektronicznego, twardych dysków komputerów, niewielkich urządzeń czy odzieży w kierunku usług finansowych, bankowych, ubezpieczeniowych i zarządzania aktywami. Bazujące na wywiadach, obserwacjach i krótkim kwestionariuszu niniejsze stadium przypadku singapurskiego biznesu dostarcza opisu stylów zarządzania i strategii komunikacyjnych 78 menedżerów reprezentujących usługi, handel detaliczny oraz przemysł. Dane ukazują, że najpowszechniejszym stylem zarządzania jest podejście oparte na zasobach ludzkich. Analiza treści, stylu i przepływu komunikacji świadczy z kolei o tym, że w Singapurze zwyczaje kulturowe, takie jak szacunek dla starszych, wychowywanie i dbanie o młodsze pokolenia, lojalność wobec rodziny i życie zgodnie z tradycjami rodzinnymi są siłami napędowymi przedsiębiorstw. Z analizy jasno wynika, że to dominująca w społeczeństwie kultura kształtuje praktyki i wartości, którym hołduje się w biznesie.
Keywords: Organizational communication; organizational management; communication in the workplace; flow of communication; communication and democracy; komunikacja w organizacji; zarządzanie organizacyjne; komunikacja w miejscu pracy; przepływ komunikacji; komunikacja i demokracja